2016
DOI: 10.1186/s40345-016-0058-0
|View full text |Cite|
|
Sign up to set email alerts
|

Online information seeking by patients with bipolar disorder: results from an international multisite survey

Abstract: BackgroundInformation seeking is an important coping mechanism for dealing with chronic illness. Despite a growing number of mental health websites, there is little understanding of how patients with bipolar disorder use the Internet to seek information.MethodsA 39 question, paper-based, anonymous survey, translated into 12 languages, was completed by 1222 patients in 17 countries as a convenience sample between March 2014 and January 2016. All patients had a diagnosis of bipolar disorder from a psychiatrist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 82 publications
1
28
1
2
Order By: Relevance
“…Although younger generations use a smartphone most frequently to perform daily activities, all age groups in an international sample preferred to use a desktop PC/ laptop for writing emails or letters, and for passing on confidential information (Bröhl et al 2018). In an international sample of patients with bipolar disorder, 81% looked for information on the Internet, with 89% of these preferring to search from a desktop/laptop (Conell et al 2016).…”
Section: Alternatives To Smartphonesmentioning
confidence: 99%
“…Although younger generations use a smartphone most frequently to perform daily activities, all age groups in an international sample preferred to use a desktop PC/ laptop for writing emails or letters, and for passing on confidential information (Bröhl et al 2018). In an international sample of patients with bipolar disorder, 81% looked for information on the Internet, with 89% of these preferring to search from a desktop/laptop (Conell et al 2016).…”
Section: Alternatives To Smartphonesmentioning
confidence: 99%
“…Patients search the internet for medical information most often to learn about side effects from prescription drugs or to obtain help from coping with their disease. (Conell et al 2016) This is especially important for patients with BD since the majority of them will inevitably turn to internet as a sources for health information. (Conell et al 2016) Our study showed that videos often lacked information regarding how to cope with the disorder and what treatment they may undergo.…”
Section: Contextmentioning
confidence: 99%
“…Moreover, although evidence is growing that internet-connected devices are increasingly owned, used and adopted by patients in the same way of the general population (Conell et al 2016 ), there is a general sense of disbelief and scepticism about the potential of these technologies in the scientific community. Notwithstanding, the number of publications and studies so far evaluating these technologies severely lacks behind peripheral biomarkers in major psychiatric disorders.…”
Section: Main Textmentioning
confidence: 99%